2011
DOI: 10.1002/btpr.633
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a subset of erythropoietin glycoforms with cytoprotective but minimal erythropoietic activity

Abstract: Although historically used for the treatment of anemia, erythropoietin (EPO) has emerged as a neurotrophic and neuroprotective agent in different conditions of neuronal damage (traumatic brain injury, ischemia, spinal cord compression, peripheral neuropathy, retinal damage, epilepsy, Parkinson's Disease, among others). Nonetheless, EPO's therapeutic application is limited due to its hematological side-effects. With the aim of obtaining EPO derivatives resembling the hormone isolated from cells and tissues of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…To overcome the unwanted erythropoietic stimulation and maintain the cytoprotective effects, non-erythropoietic analogs have been synthetized via chemical modifications of EPO. These analogs include carbamylated EPO (CEPO), glutaraldehyde EPO –obtained by chemical modification of the lysine residues-, Neuro-EPO – an analog with low sialic acid content-, EPOL – a variant with low glycosylation- and neuropoietin – a less acidic EPO isoform (Leist et al, 2004; Mattio et al, 2011; Rodriguez Cruz et al, 2017; Castillo et al, 2018; Ercan et al, 2018). Recently, smaller EPO-mimetic have also been developed.…”
Section: Erythropoietin As Therapeutic Compoundmentioning
confidence: 99%
“…To overcome the unwanted erythropoietic stimulation and maintain the cytoprotective effects, non-erythropoietic analogs have been synthetized via chemical modifications of EPO. These analogs include carbamylated EPO (CEPO), glutaraldehyde EPO –obtained by chemical modification of the lysine residues-, Neuro-EPO – an analog with low sialic acid content-, EPOL – a variant with low glycosylation- and neuropoietin – a less acidic EPO isoform (Leist et al, 2004; Mattio et al, 2011; Rodriguez Cruz et al, 2017; Castillo et al, 2018; Ercan et al, 2018). Recently, smaller EPO-mimetic have also been developed.…”
Section: Erythropoietin As Therapeutic Compoundmentioning
confidence: 99%
“…However, production of recombinant EPO results in a complex mixture of glycoforms, where the primary protein sequence and the glycosylation sites are highly conserved but the carbohydrate domains present significant heterogeneity. Despite studies suggesting that specific sugar modifications affect the stability and erythropoietic activity of EPO [96, 97], the unavailability of single glycoforms has complicated elucidation of the relationship between EPO glycosylation and its biological activity. Chemical synthesis uniquely holds the potential to provide access to homogeneous EPO for systematic evaluation of the effect of the glycan structure on biological activity.…”
Section: Chemical Synthesis Of Glycoproteinsmentioning
confidence: 99%
“…Development of derivatives of EPO that do not bind to the classical EPOR (carbamylated erythropoietin or CEPO) or that have such a short half-life in the circulation that erythropoiesis is not significantly stimulated (asialoerythropoietin or neuroepoietin) have clearly demonstrated that the neuroprotective effects of EPO can be separated from the hematopoietic effects (Leist et al, 2004; Erbayraktar et al, 2003; Mattio et al, 2011). In 2004, Brines et al showed that mice deficient in the common beta (CD131) receptor exhibited no neuroprotection with EPO, and suggested that these activities might be mediated by a heteroreceptor complex of the classical EPOR and the CD131 receptor (Brines et al, 2004).…”
Section: Non-erythropoietic Derivatives Of Epomentioning
confidence: 99%